2013
DOI: 10.1002/jmv.23728
|View full text |Cite
|
Sign up to set email alerts
|

Clinical relevance and genotypes of circulating noroviruses in northern Taiwan, 2006–2011

Abstract: The incidence of noroviral gastroenteritis has increased dramatically in recent years, and norovirus (NoV) genogroup II.4 (GII.4) is associated with outbreaks worldwide. The NoV genotypes and their clinical relevance in children hospitalized with acute gastroenteritis between 2006 and 2011 in northern Taiwan were evaluated in this study. NoV sequences were amplified from 47 clinical specimens and phylogenetic analysis was performed. Based on noroviral capsid protein (VP1) and RNA dependent RNA polymerase (RdRp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 44 publications
0
15
1
Order By: Relevance
“…Overall, the limitation is that number of cases in this study is small and there may be a bias, more investigation is needed in future. Almost all of the epidemiological studies show that GII.4 norovirus was the predominant genotype identified in presented genotyping data [33,34]. However, in this study, the total detection rate of GII.3 norovirus was reached 50%.…”
Section: Discussioncontrasting
confidence: 62%
“…Overall, the limitation is that number of cases in this study is small and there may be a bias, more investigation is needed in future. Almost all of the epidemiological studies show that GII.4 norovirus was the predominant genotype identified in presented genotyping data [33,34]. However, in this study, the total detection rate of GII.3 norovirus was reached 50%.…”
Section: Discussioncontrasting
confidence: 62%
“…The genetic and environmental interactions of the intestinal microbiota are reportedly correlated with the progression of inflammatory bowel disease9. Acute viral gastroenteritis (AGE) can be associated with atypical manifestations, such as convulsions and intestinal hemorrhage101112. Recent studies found that the adaptive responses against commensals consist integral component of mucosal immunity in gastrointestinal infection, and following norovirus infection, patients who have a disrupted microbiota may be at elevated risk for long-term health complications1314.…”
mentioning
confidence: 99%
“…In recent years, GII.Pg norovirus has been widely documented in individuals with gastroenteritis as well as in environmental samples. Reports of the detection of GII.Pg norovirus in humans include studies in Australia [Eden et al, 2010;Dunbar et al, 2014;Lodo et al, 2014], Belgium [Mathijs et al, 2011], China [Mei et al, 2011;Sang et al, 2014], France [Loury et al, 2015], Germany [Hoffmann et al, 2013], Italy [Medici et al, 2014], South Africa [Mans et al, 2014], Spain [Arana et al, 2014], Taiwan [Tsai et al, 2014], Tanzania [Moyo et al, 2014], and the United States [Takanashi et al, 2011]. GII.Pg norovirus has also been detected in sewage and surface waters in Argentina [Blanco Fernandez et al, 2011.…”
Section: Discussionmentioning
confidence: 99%
“…One genotype identified by ORF 1 nucleotide sequencing has been termed “GII.Pg.” It appears to be an obligatory recombinant, in that no unique GII.g ORF 2 sequence has been identified. So far, various studies have linked GII.Pg to two ORF 2 genotypes, GII.1 [Mathijs et al, ; Giammanco et al, ; Hoffmann et al, ; Lodo et al, ; Medici et al, ] and GII.12 [Mei et al, ; Takanashi et al, ; Arana et al, ; Medici et al, ; Sang et al, ; Tsai et al, ]. However, detailed studies on the emergence and molecular epidemiology of GII.Pg noroviruses are lacking and the precise relationship between the GII.Pg ORF 1 genotype and its ORF 2 recombinant forms has not been studied in detail.…”
Section: Introductionmentioning
confidence: 99%